Cultural policies in Galicia: handicraft accreditation - Paz,Elena Freire (2022)
Abstract In this paper we propose to describe and analyse the cultural policies implemented in Galicia as survival strategies within the European Union over the past 30 years. In this institutional regard we believe intervention has allowed for a legitimization of political power at the same time as it provided its own identity credentials based on the difference of being able to operate from an economic level in two ways. First, encouraging the shift of the production network to the tertiary sector, and second, serving as brand image in the tourism sector. In these complex dynamics with polyhedral interests which are a controversial subject of debate on a local vs. global, economic vs. political, social vs. cultural level, we will investigate what is the margin granted to the levels of authenticity which the production of current Galician crafts may present.